Pengaruh Environmental Accounting Management Information dan Activity Based Costing Terhadap Kinerja Lingkungan Melalui Mediasi Kualitas Keputusan - Febiyan, Vina; Indrati , Menik (Syntax Literate, 2025)
This study investigates the influence of the relationship between Environmental Accounting Management Information and Activity Based Costing on Environmental Performance, considering Decision Quality as a mediating factor. This study uses a sample of 170 respondents by selecting research subjects from Micro, Small, and Medium Enterprises (MSMEs) in the Jabodetabek area. The research method employed a quantitative technique through primary data from surveys, which were then analyzed using the Structural Equation Model (SEM). The model selection used Descriptive Statistikal Tests, Model Measurement Hypothesis Tests, Structural Model Hypothesis Tests, and Panel Data Hypothesis Tests. The study results reveal that Environmental Accounting Management Information and Activity Based Costing have a positive impact on environmental performance, Decision Quality has a positive impact on Environmental Performance, and Decision Quality is identified as a mediating factor that can strengthen the relationship between Environmental Accounting Management Information, Activity Based Costing, and better Environmental Performance. Environmental performance serves as a signal for management to analyze environmental information in business operations through the implementation of Environmental Accounting Management Information and Activity Based Costing systems. The implementation of Activity Based Costing and Environmental Accounting Management Information systems supports business resource efficiency strategies by focusing on environmental performance. Decision quality signals management at all levels to make more accurate decisions about environmental performance. These findings contribute to the development of more sustainable managerial strategies and support the integration of environmental accounting information. It is hoped that the results of this research can contribute positively to higher quality decision-making and have a positive integration in managing environmental issues for SMEs in the Jabodetabek area.